Knowledge brokering to bridge the research-practice gap in education: Where are we now? - Rycroft-Smith, Lucy (Review of Education, 2022)
Connecting research to practice by knowledge brokering in education, which is considered here as functionally synonymous with knowledge mobilisation, is currently under-researched, difficult to define, and not well understood. This narrative synthesis review curates recent research concerning characterisations of knowledge brokering in education, considering the models and metaphors that have been used to describe and prescribe its activities, and then goes on to consider the limited evidence on effective knowledge brokering and what this suggests about possibilities for its evaluation in education contexts, which is considered necessary and urgent. Interpersonal relationships and social contexts are considered key to educational knowledge brokering, which has also been described as transforming knowledge, often by mediation, boundary-spanning, and/or bridging. It is suggested that those doing the work of knowledge brokering (knowledge brokers) should have a deep understanding of the context and terrain of both research and practice (and perhaps policy) in education. A need is proposed for theoretical and empirical work to define the purposes and pitfalls of educational knowledge brokering in practice, related to issues of trust and credibility, and to enable evaluation and accountability to take place.
Keywords: knowledge brokering; knowledge mobilisation; knowledge translation